2013
DOI: 10.1158/0008-5472.can-12-3840
|View full text |Cite|
|
Sign up to set email alerts
|

miR145 Targets the SOX9/ADAM17 Axis to Inhibit Tumor-Initiating Cells and IL-6–Mediated Paracrine Effects in Head and Neck Cancer

Abstract: ALDH1þ CD44 þ cells are putative tumor-initiating cells (TIC) in head and neck squamous cell carcinomas (HNC). miR-145 regulates tumorigenicity in various cancers but the breadth of its mechanistic contributions and potential therapeutic applications are not completely known. Here, we report that ALDH1 þ CD44 þ -HNC cells express reduced levels of miR145. SPONGE-mediated inhibition of miR-145 (Spg-miR145) was sufficient to drive tumor-initiating characteristics in non-TICs/ALDH1 À CD44-negative HNC cells. Mech… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
140
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(146 citation statements)
references
References 49 publications
3
140
1
Order By: Relevance
“…Here we demonstrated that miR-145 biogenesis can be regulated by lncRNA-LET/NF90 axis. Although it is known that miR-145 negatively regulates human embryonic stem cells and CSCs, it is unclear whether it regulates the stemness markers indirectly or directly (45)(46)(47)(48). We demonstrated in this report that in UBC cells KLF4 and HMGA2, two miR-145 targets, are responsible for miR-145 mediated inhibition of UBC cell stemness.…”
Section: Discussionmentioning
confidence: 66%
“…Here we demonstrated that miR-145 biogenesis can be regulated by lncRNA-LET/NF90 axis. Although it is known that miR-145 negatively regulates human embryonic stem cells and CSCs, it is unclear whether it regulates the stemness markers indirectly or directly (45)(46)(47)(48). We demonstrated in this report that in UBC cells KLF4 and HMGA2, two miR-145 targets, are responsible for miR-145 mediated inhibition of UBC cell stemness.…”
Section: Discussionmentioning
confidence: 66%
“…1), suggesting that GKN1 may downregulate SOX9 expression by inhibiting the b-catenin signaling pathway. However, it has also been reported that additional regulatory molecules, including miR-145 and NF-jB subunit p65, also contribute to the regulation of SOX9 expression [18,19], Thus, additional studies are necessary to verify these initial observations.…”
Section: Discussionmentioning
confidence: 99%
“…3 Emerging evidence has shown that miRNAs are involved in cancer initiation and progression. 4 MiR-145 has been reported as an important tumor suppressor gene in ovarian carcinoma, 5,6,7 malignant pleural mesothelioma, 8 breast cancer, 9 pancreatic cancer, 10,11 liposarcoma, 12 colorectal cancer, 13,14,15,16 neuroblastoma, 17 breast cancer, 18,19,20,21 esophageal cancer, 22 bladder cancer, 23,24 urothelial cancer, 25 prostate cancer, 26,27 gastric cancer, 28 and head and neck cancer, 29 and other types. MiR-145 was also implicated in the progression of NSCLC; 30,31,32 however, its exact mechanism is not well established.…”
Section: Introductionmentioning
confidence: 99%